A low selenium level is associated with lung and laryngeal cancers. - Katrzyna Jaworska (Public Library of Science (PLoS), 2013)
Purpose It has been suggested that selenium deficiency is a risk factor for several cancer types. We conducted a case-control study in Szczecin, a region of northwestern Poland, on 95 cases of lung cancer, 113 cases of laryngeal cancer and corresponding healthy controls. Methods We measured the serum level of selenium and established genotypes for four variants in four selenoprotein genes (GPX1, GPX4, TXNRD2 and SEP15). Selenium levels in the cases were measured after diagnosis but before treatment. We calculated the odds of being diagnosed with lung or laryngeal cancer, conditional on selenium level and genotype. Results Among lung cancer cases, the mean selenium level was 63.2 µg/l, compared to a mean level of 74.6 µg/l for their matched controls (p<0.0001). Among laryngeal cancer cases, the mean selenium level was 64.8 µg/l, compared to a mean level of 77.1 µg/l for their matched controls (p<0.0001). Compared to a serum selenium value below 60 µg/l, a selenium level above 80 µg/l was associated with an odds ratio of 0.10 (95% CI 0.03 to 0.34; p = 0.0002) for lung cancer and 0.23 (95% CI 0. 09 to 0.56; p = 0.001) for laryngeal cancer. In analysis of four selenoprotein genes we found a modest evidence of association of genetic variant in GPX1 with the risk of lung and laryngeal cancers. Conclusion A selenium level below 60 µg/l is associated with a high risk of both lung and laryngeal cancer.